Mobile devices to increase attention and improve learning - Bonaiuti, Giovanni; Ricciu, Roberto (Form@re - Open Journal per la formazione in rete, 2017)
The paper presents a research carried out at the University of Cagliari during two academic years. The aim was to analyse the effect on students learning resulting from the introduction of a method based on questions and answers in a traditional large-classroom lecture. We investigated whether an interactive teaching approach, facilitated by an interactive software application based on mobile technologies, would lead to improved student engagement and learning outcomes in large-group of environmental engineering science lectures for undergraduate students. The goal was to assess the impact on learning outcomes, as well as the acceptance and appreciation of the students, of a lecture intermixed with questions and answers followed by analysis and discussion of the answers. In our experience we compared two different application of this methodology: with and without technology. The results obtained, in turn, were compared with those of a traditional lecture. Dispositivi mobili per aumentare l’attenzione e migliorare l’apprendimento Il contributo presenta una ricerca svolta all’Università di Cagliari nel corso di due anni accademici tesa ad analizzare le potenzialità di una modalità di lezione basata sull’uso frequente di “domande e risposte” gestite attraverso tecnologie. Abbiamo cercato di capire se un approccio didattico più interattivo, facilitato da un’applicazione software basata su tecnologie mobili, riesca a migliorare il coinvolgimento degli studenti e i risultati di apprendimento, in un contesto caratterizzato da un elevato numero di partecipanti. L’obiettivo era quello di verificare l’impatto sui risultati di apprendimento, oltre all’accettazione ed all’apprezzamento da parte degli studenti, di una didattica frontale intervallata da domande di verifica e dalla conseguente analisi e discussione delle risposte. Nell’esperienza sono state comparate due diverse modalità di applicazione di questa metodologia: con e senza le tecnologie e, i risultati ottenuti, sono a loro volta stati confrontati con quelli di una lezione tradizionale.